2007
DOI: 10.1371/journal.pone.0000528
|View full text |Cite
|
Sign up to set email alerts
|

Switching on the Lights for Gene Therapy

Abstract: Strategies for non-invasive and quantitative imaging of gene expression in vivo have been developed over the past decade. Non-invasive assessment of the dynamics of gene regulation is of interest for the detection of endogenous disease-specific biological alterations (e.g., signal transduction) and for monitoring the induction and regulation of therapeutic genes (e.g., gene therapy). To demonstrate that non-invasive imaging of regulated expression of any type of gene after in vivo transduction by versatile vec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…[6][7][8] Using engineered lentiviral vectors co-expressing the mutant epidermal growth factor receptor variant III and reporters consisting of green fluorescent and Renilla luciferase proteins, a group of researchers showed that there is a direct correlation between epidermal growth factor receptor expression and glioma cell proliferation in the initial stages of glioma progression. 9 Winkeler et al 10 have reported the feasibility of monitoring the dynamics of regulated gene expression mediated by herpes simplex virus type 1 (HSV-1) amplicon vectors after in vivo transduction in experimental gliomas. All of these studies require co-expression of reporter gene with gene of interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] Using engineered lentiviral vectors co-expressing the mutant epidermal growth factor receptor variant III and reporters consisting of green fluorescent and Renilla luciferase proteins, a group of researchers showed that there is a direct correlation between epidermal growth factor receptor expression and glioma cell proliferation in the initial stages of glioma progression. 9 Winkeler et al 10 have reported the feasibility of monitoring the dynamics of regulated gene expression mediated by herpes simplex virus type 1 (HSV-1) amplicon vectors after in vivo transduction in experimental gliomas. All of these studies require co-expression of reporter gene with gene of interest.…”
Section: Introductionmentioning
confidence: 99%
“…All of these studies require co-expression of reporter gene with gene of interest. This can be achieved by two coordinately acting promoters, [10][11][12] gene fusion 13 and by including proteolytic cleavable sites such as fusagene or translational linkers such as the internal ribosome entry site (IRES) or self-processing peptides. 14 Over the last 10 years, the IRES element has been the most common way to express multiple genes in a single vector.…”
Section: Introductionmentioning
confidence: 99%
“…There is an urgent need for the regulation of transgene expression which can be achieved either with the use of specific promoters or with the utilization of regulatory elements that can be controlled exogenously through systemic drug administration (Goverdhana et al, 2005). The expression of the transgene can be coupled with advance in vivo monitoring of expression levels in order to be able to detect signaling pathway alteration after viral administration and in combination with a controllable expression system to manipulate the course of the tumor progression (Winkeler et al, 2007). There is currently an emerging field of research that is focusing on the use of carrier cells for viral delivery to tumor sites.…”
Section: Hurdles For the Use Of Viruses As Delivery Vectorsmentioning
confidence: 99%
“…Although the effect of amplicon vector genome size on packaging efficiency has only been studied using smaller plasmids [108], indirect data suggest that as much as 160 kb may be carried within HSV-1 particles [28] and smaller constructs are packaged as multimers with a sum length closest to the full capsid capacity (reviewed in [105]). The exciting implications of this have already been illustrated by novel amplicon vectors carrying (1) whole genomic loci which retain their normal regulation by metabolite ligands when introduced into cultured fibroblasts [109] or stable longterm expression at physiological levels in the adult mammalian brain [110]; (2) multiple genetic elements including a double tetracycline-responsive system (both activator and silencer), two fluorescent protein reporters, a positron emission tomography (PET) marker gene and chromatin isolating elements [111]; (3) heterologous elements from AAV [112], EBV [113], cellular scaffold/matrix attachment regions (S/MARs) [114] and human alphoid DNA sequences [115] to confer new modes of vector maintenance in target cells (reviewed in [116]); (4) whole packaging systems for other viral vectors, opening up the possibility of viral "launchers" which after infecting a primary target cell are able fire off smaller vectors to extend gene delivery to secondary target cells [117][118][119]. Amplicon vectors have had a special niche in gene transfer for research applications because of their easy construction as simple plasmids.…”
Section: Amplicon Vectors: Transgenes In Plasmidsmentioning
confidence: 99%